Acquired agminated melanocytic nevus in the acral area is a potential mimicker of acral lentiginous melanoma: A three‐case series report and published work review. Issue 7 (4th May 2020) - Ogawa, Kohei; Fujimoto, Masakazu; Takai, Toshihiro; Mitsui, Yasuhiro; Iwasa, Kentaro; Ohsita, Akifumi; Komori, Satoshi; Asai, Jun; Azukizawa, Hiroaki; Miyagawa, Fumi; Yurugi, Satoshi; Kuwahara, Masamitsu; et al.
Abstract: Agminated nevus refers to a clustered group of melanocytic nevi confined to a localized area of the body. It rarely involves acral skin, but recognition of acquired agminated nevus (AAN) in the acral area is clinically important because it may mimic acral lentiginous melanoma (ALM). However, acral AAN has only been described in a few case reports and its clinical characteristics remain unclear. We report three additional cases of acral AAN to further analyze the differential points between ALM. Clinical images, including those of dermoscopy, of three cases of acral AAN were reviewed. The lesions were located on the sole or lateral border of the foot. All acral AAN were flat and large in size (>20 mm in greatest dimension), and associated with asymmetry and irregular border. However, no parallel ridge pattern suggesting ALM was observed on dermoscopy. In two patients, the lesions on the sole were totally resected; microscopic evaluation of these two lesions confirmed junctional nests of banal melanocytes. AAN lesions on the sole with chronic mechanical pressure are slightly larger and more diffuse; thus, they may be more likely to be overdiagnosed as malignancy upon inspection than those in the non‐acral area. Understanding the concept of the disease and careful dermoscopic evaluation leads to an accurate diagnosis.